Restructuring Public Financial Management Institutional Arrangements : A Case for Separation of Accounting from Auditing Functions, Government of Bangladesh - World Bank (Washington, DC, 2013)
This Policy Note focuses on how the Government of Bangladesh can respond in the context of growing demand for better financial management performance, by strengthening the accounting and auditing functions of the government through a distinct cadre. The note also proposes the broader role of the accounting and auditing function in view of contemporary reform in the areas of public financial management and necessary institutional framework that needs to be in place before separation takes place. In addition to these, the note also provides the Government with updated information on the current state of the accounting function vis-a-vis the accounting and auditing cadre and the essential pre-requisites that would need to be addressed before full separation of the cadre is initiated. It sets out policy decisions that need to be taken on a priority basis to accelerate the separation process.